Laparoscopic treatment of median arcuate ligament syndrome without ganglionectomy of the celiac plexus in the hybrid operating room: Report of a case. (April 2021) - Kayashima, Hiroto; Minagawa, Ryosuke; Inokuchi, Shoichi; Koga, Tadashi; Miura, Nobutoshi; Kajiyama, Kiyoshi
Highlights: The treatment of median arcuate ligament syndrome is the surgical release of the ligament. Symptomatic patients need the ligament release with wide excision of the celiac plexus. However, the majority of the patients with celiac artery compression remains asymptomatic. It might be enough to just release the ligament without ganglionectomy for asymptomatic patients. Hybrid operating room could allow for adequate ligament release without ganglionectomy. Abstract: Introduction: Median arcuate ligament syndrome (MALS) is a rare condition in which the median arcuate ligament (MAL) causes compression of the celiac artery (CA) and plexus. Although 13–50 % of healthy population exhibit radiologic evidence of the CA compression, the majority remains asymptomatic. With or without symptoms, MALS have a risk of developing collateral circulation that leads to pancreaticoduodenal artery (PDA) aneurysms that have high risk of rupture. The treatment of MALS is the surgical release of the MAL. However, the necessity of ganglionectomy of the celiac plexus is still unclear. Presentation of case: A 60-year-old man with a ruptured PDA aneurysm caused by MALS was admitted to our hospital for an emergency. After treatment for the ruptured PDA aneurysm by transcatheter arterial coil embolization, he underwent elective laparoscopic MAL release in the hybrid operation room to check blood flow of the CA intraoperatively. The angiography of the CA immediately after MAL release without ganglionectomy of the celiac plexus showed the antegrade blood flow to the proper hepatic artery instead of the retrograde flow via the pancreaticoduodenal arcade. The postoperative course was uneventful and the follow-up computed tomography revealed no residual CA stenosis. Discussion: Unlike symptomatic MALS, it might be enough to just release the MAL without ganglionectomy of the celiac plexus for asymptomatic MALS, especially that with the treated PDA aneurysm. Conclusion: Laparoscopic treatment of MALS in hybrid operating room could allow for adequate MAL release without ganglionectomy of the celiac plexus using the intraoperative angiography of the CA.